Analisis Perubahan Karakter Siswa Terhadap Pembelajaran Akidah Akhlak - Muhammad Zaki Hanif Mahfuzh; Bunyamin Bunyamin (Journal on Education, 2024)
This research aims to analyze the extent of students' character changes towards the learning of Akidah Akhlak (Faith and Morality). The research method used in this study is a qualitative descriptive research method with a case study approach (Field) using observation and interview methods. Data sources consist of primary (main) and secondary (supporting) data, with the research conducted at a school located in SMA Muhammadiyah 23 East Jakarta. The data collection technique to determine the research subjects is triangulation, which involves data collection, data reduction, data presentation, and conclusion drawing. This technique is chosen to ensure data validity by comparing interview results with the research object. The research findings indicate that the planning of Akidah Akhlak teacher's learning in character formation efforts in students involves designing lesson plans involving media and also demonstrating good manners so that students can also apply them directly. The implementation of Akidah Akhlak learning with the aim of forming student character has been carried out by referring to the rules and regulations applied in every activity or learning process in each educational institution. Evaluation of Akidah Akhlak teacher's learning includes assignments and practices given by teachers, daily tests, mid-term tests, and final tests for students. The delivery of Akidah Akhlak learning in shaping student character applied by subject teachers at SMA Muhammadiyah 23 has yielded very satisfactory results, allowing students to gradually form their characters well and practice them in the school environment.